1997
DOI: 10.1089/ees.1997.14.141
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acid-Mine Water with Calcite and Quartz Sand

Abstract: This study investigates interactions between a typical acid-mine water and a solid mixture of calcite and quartz. In this solid mixture, calcite provides a source of alkalinity whereas quartz surfaces become preferable place for precipitation of produced oxides. The results indicate that neutralization by calcite dissolution is critical for extensive immobilization of metals from these waters. As pH increases, ferrihydrite, amorphous Al(OH)3, Cu(OH)2, and possibly Zn(OH)2 precipitate that decreases the aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The results of Duncan's Multiple Range test (Table 5) showed that the means of the filter types, solution types and temperatures were significantly different from one another at a 95 % confidence level. Although several researchers [10,11] suggested that the use of a mixture of limestone and sandstone to treat iron contaminated wastewater in order to avoid armoring of limestone and to increase the lifetime of the filter, the result obtained from this study showed that increasing the percent of limestone in the filter from50% to 100% increase the iron removal rate constant by 38%. The precipitation reaction of ferric hydroxide (Fe(OH) 3 ) produced protons that would consequently decrease the pH of the solution and increase the solubility of Fe(OH) 3 .…”
Section: Ironmentioning
confidence: 67%
“…The results of Duncan's Multiple Range test (Table 5) showed that the means of the filter types, solution types and temperatures were significantly different from one another at a 95 % confidence level. Although several researchers [10,11] suggested that the use of a mixture of limestone and sandstone to treat iron contaminated wastewater in order to avoid armoring of limestone and to increase the lifetime of the filter, the result obtained from this study showed that increasing the percent of limestone in the filter from50% to 100% increase the iron removal rate constant by 38%. The precipitation reaction of ferric hydroxide (Fe(OH) 3 ) produced protons that would consequently decrease the pH of the solution and increase the solubility of Fe(OH) 3 .…”
Section: Ironmentioning
confidence: 67%
“…Sorption appears as a simple and low-cost method, with a great potential of becoming an actual alternative to conventional ones, overcoming the problems of insufficient efficiency and difficult waste handling derived from the precipitation method. Different materials have been subject of study in this regard, most of them can be classified in two groups, bio-materials, such as agricultural by-products [8][9][10][11][12], algae [13][14][15][16], fungi [17] and chitin based sorbents [18,19], and minerals, such as iron hydroxides and oxyhydroxides [20][21][22], aluminium hydroxides and oxides [23,24], clays [25][26][27][28][29][30], zeolites [31][32][33], calcite [34,35] and wollastonite [36,37]. In general, bio-materials display higher Cd sorption capacity values, which could make their use in purification systems preferable face to minerals; nevertheless, most bio-materials present the important shortcoming of being affected by the place or season of harvesting and by the growing conditions [38], what could limit greatly their application.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al [12] used limestone filters to treat contaminated groundwater containing iron concentration of 5 mg L¯1 and reported final concentration of iron of 0.2 mg L¯1. Xu et al [13] conducted batch experiments using calcite and quartz grains as filter media and reported an iron removal efficiency of 99.8%. Sun [`10] conducted batch experiments in which limestone was used as a filter medium to treat an iron acid solution (27.9 mg iron L¯1) and reported an iron removal of 100% after 150 minutes.…”
Section: Ironmentioning
confidence: 99%
“…The significance of including sandstone in the filter is to minimize the metal hydroxide armoring of the limestone and thus increase the useful lifetime of the filter. Xu et al [13] and Sasowsky et al [14] reported that iron preferentially precipitates on the sandstone Surface and concluded that the surface charge of calcite and ferrihydrite are positive and the surface charge of quartz is negative over the pH range of 2 -8. In this study, the effects of sandstone addition and armoring on the removal efficiency were not evident due to the short duration of the experiment.…”
Section: Ironmentioning
confidence: 99%